Development of theraputic aid using 3D printing - Theng, Herman Wen Jun (Nanyang Technological University, 2021)
Hospitals are constantly on the lookout for innovative and efficient ways to improve the hospital experience for children, the countless treatment processes that these children must endure can be scarring. To allay fears and increase the child’s ability to cope, hospitals will engage them in play therapy and psychoeducation using modified aids to enable a more constructive response to the experiences associated with cancer treatment. However, play therapists often use antiquated or hand-crafted improvised aids as props, limited to whatever they have available. Hence, this project was set to establish a better way of developing therapeutic aids and expanding the forms of aids that can be used to prepare paediatric patients before the actual procedure. A study was done in two phases: 1. Understanding the use of 3D printing to develop a MIBG model aid; 2. Development of Extend Reality (XR) platforms and evaluating its effectiveness in therapy. Products from both phases were subsequently introduced to CCF as aids to facilitate play therapy. Through phase one, 3D printing was found to benefit the production more than traditional manufacturing methods. It was a cheaper and faster way to develop such aids as it allows for better customisation and freedom when designing – not all aids follow the same standard and had to be designed to cater for different needs. During the second phase, a 360-degree video and Augmented Reality (AR) application was developed, these platforms were introduced as an up-and-coming technology that has the ability to improve play therapy. Overall, the printed model had positive reactions and was successfully incorporated into play therapy sessions with minimum improvements required. On the other hand, XR was proven to be a good enhancement in the field of therapy and could be implemented towards a specific age of paediatric patients. Spurring for more research to be done in this direction before it can be permanently implemented.